Post-Conflict Reparation: Ukrainian Restitution Remedies for Property and Restitution Complaints before the European Court of Human Rights - Antsupova, Tetyana (Kyiv-Mohyla Law and Politics Journal, 2016)
This article describes the proposed Ukrainian legislation on national remedies for the restitution of property damaged or destroyed during the conflicts in Eastern Ukraine and Crimea. Noting gaps in this proposed legislation, it emphasizes the need for an effective National Strategy for post-conflict reparations and a related Action Plan. The article also analyzes the European Court of Human Rights’ decision in Lisnyy and Others v. Ukraine and Russia, in which the Court ruled inadmissible for want of evidence the applicants’ complaints about the shelling of their homes in Eastern Ukraine during the hostilities there that began in April 2014. The article concludes by examining the Lisnyy and Others v. Ukraine and Russia decision’s implications for a national remedy for the restitution of property damaged or destroyed during the ongoing hostilities.